Finger sucking habit: Prevalence, contributing factors and effect on occlusion - Alaa D Al-Dawoody (University of Mosul, College of Dentistry, 2004)
The aims of this study were to find the prevalence of finger sucking habit among primary school children and to detect the effect of some factors like parents' occupation, socioeconomic status of the family, pacifier use, feeding method and child rank on the occurrence of the habit. Effects of finger sucking habit on occlusion were also looked for. The prevalence of finger sucking ha-bit was looked for in 1780 students (1030 boys and 750 girls) in six primary schools randomly selected in the center of Mosul City. The age of the students ranged bet-ween 6-14 years, with a mean of 10.2 years. The habit was noted in 5.56% of the students, with significant female preponderance.In comparison with a nearly identical control group, finger-sucking habit was significantly higher in those, whose mothers were officials, those who were on bottle-feeding and those who were not using pacifier. No significant influence of father's occupation, children birth rank and economic status of the family on the prevalence of finger sucking habit was noted. Finger suckers showed a significant increase in over jet, anterior open bite and decrease in deep bite and lower arch spacing. No significant difference was noted between finger suckers and the control group with respect to upper anterior spacing, upper and lower crowding and posterior cross bite.